Cover Image: Volume 20, Issue 1. Issue 1 (16th September 2020) - Unknown
Abstract : Cover image : "The defensive caste of the Eastern subterranean termite. Soldiers are specialized for defence of their colony, as evidenced by their assertive behaviour, enlarged heads and fortified mandibles. The three individuals shown here, positioned atop a small piece of wood, are collected from a colony in the City of Toronto (Canada), where termites are considered an invasive pest."